Assessment of Gastronomic Tourism Potential in the Ganja-Gazakh Economic Region of Azerbaijan - ALIYEV, Vasif (Journal of Environmental Management and Tourism; Vol 13 No 4 (2022): JEMT, Volume XIII, Issue 4(60), Summer 2022DO - 10.14505/jemt.v13.4(60).20, 2022)
We have shifted our focus away from the sea-sand-sun triad and toward other tourist kinds as a result of shifting tourism trends throughout the world and in our own country. Gastronomy tourism can bring visitors to the location at any time of year. Because it is not affected by seasonality, it is a step ahead of other forms of tourism in this respect. Lack of promotion in determining the gastronomic potential of the Ganja-Gazakh economic region of Azerbaijan and highlighting gastronomic values, the presence of a bad image in English about the importance of the Ganja province, the lack of collection of gastronomic delicacies under one roof, mainly meat and meat products included in the target values, the lack of sufficient government support for tourism. There are no gastronomic holidays, etc. Among the negative results obtained as a result of the study are such problems as the inadequacy of the physical conditions in the activity. The Ganja-Gazakh economic region is one of the factors that positively influence the Ganja-Gazakh economic region due to its geographical location, having fertile lands, many civilizations, cultural and historical structure and unique cooking techniques. The purpose of this study, which analyzes the unique features and defining factors of the modern tourism industry that has developed around gastronomy,based on the study of existing market structures as well as future developments. The research method chosen for this purpose is a case study analysis at both empirical and theoretical levels. The example of the Ganja-Kazakh economic region, where gastronomic tourism has developed recently with its unique characteristics, provides a suitable basis for proposing a strategic plan to develop the industry by using the dynamics of its great potential.